(8x+10)-(3x+1)=

Simple and best practice solution for (8x+10)-(3x+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8x+10)-(3x+1)= equation:


Simplifying
(8x + 10) + -1(3x + 1) = 0

Reorder the terms:
(10 + 8x) + -1(3x + 1) = 0

Remove parenthesis around (10 + 8x)
10 + 8x + -1(3x + 1) = 0

Reorder the terms:
10 + 8x + -1(1 + 3x) = 0
10 + 8x + (1 * -1 + 3x * -1) = 0
10 + 8x + (-1 + -3x) = 0

Reorder the terms:
10 + -1 + 8x + -3x = 0

Combine like terms: 10 + -1 = 9
9 + 8x + -3x = 0

Combine like terms: 8x + -3x = 5x
9 + 5x = 0

Solving
9 + 5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 5x = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 5x = 0 + -9
5x = 0 + -9

Combine like terms: 0 + -9 = -9
5x = -9

Divide each side by '5'.
x = -1.8

Simplifying
x = -1.8

See similar equations:

| y/3-5=1 | | 7y=x-3 | | 26+6k=14 | | 3D+8=2dminus-17 | | -0.25x+0.10y=1.05 | | =5.6 | | r+11+8r=25 | | r+11+8r=2555555555555 | | 22m+22=30 | | N(x)=-0.3x^2+9x+15 | | 1/2x-5=-17 | | 6x+2=CBD | | (20x^-3)/(2x^-5) | | log[3](x-5)+log[3](x+3)=2 | | 1/2(ln2-ln1) | | 77/s=132/48 | | -x^2+x-18= | | X/4=80 | | 0.7x=0.864 | | -4(4y-5)+3(3y+5)= | | 8/t=840/210 | | 9p=96 | | 2x^2-3x+.05=0 | | e^4=y | | 250y-y^2=10000 | | A/5=105 | | y/493=228/116 | | 664/996=r/12 | | N/2=33 | | 15n-125=175 | | 4x-3y/8z | | 1=3-d |

Equations solver categories